Śrīśatruñjaya girirāja darśana ane śilpasthāpatyakalāmāṃ Śrīśatruñjaya - Kanchansagarsuri (Śrīāgamoddhāraka granthamālā ;, 1982)
On the history, architecture, and religious significance of Satrunjaya hill, a jain pilgrimage center.